Activities of daily living associated with acquisition of melioidosis in northeast Thailand: a matched case-control study. - Direk Limmathurotsakul; Manas Kanoksil; Vanaporn Wuthiekanun; Rungrueng Kitphati; Bianca deStavola; Nicholas P J Day; Sharon J Peacock (Public Library of Science (PLoS), 2013)
Melioidosis is a serious infectious disease caused by the Category B select agent and environmental saprophyte, Burkholderia pseudomallei. Most cases of naturally acquired infection are assumed to result from skin inoculation after exposure to soil or water. The aim of this study was to provide evidence for inoculation, inhalation and ingestion as routes of infection, and develop preventive guidelines based on this evidence.A prospective hospital-based 1∶2 matched case-control study was conducted in Northeast Thailand. Cases were patients with culture-confirmed melioidosis, and controls were patients admitted with non-infectious conditions during the same period, matched for gender, age, and diabetes mellitus. Activities of daily living were recorded for the 30-day period before onset of symptoms, and home visits were performed to obtain drinking water and culture this for B. pseudomallei. Multivariable conditional logistic regression analysis based on 286 cases and 512 controls showed that activities associated with a risk of melioidosis included working in a rice field (conditional odds ratio [cOR] = 2.1; 95% confidence interval [CI] 1.4-3.3), other activities associated with exposure to soil or water (cOR = 1.4; 95%CI 0.8-2.6), an open wound (cOR = 2.0; 95%CI 1.2-3.3), eating food contaminated with soil or dust (cOR = 1.5; 95%CI 1.0-2.2), drinking untreated water (cOR = 1.7; 95%CI 1.1-2.6), outdoor exposure to rain (cOR = 2.1; 95%CI 1.4-3.2), water inhalation (cOR = 2.4; 95%CI 1.5-3.9), current smoking (cOR = 1.5; 95%CI 1.0-2.3) and steroid intake (cOR = 3.1; 95%CI 1.4-6.9). B. pseudomallei was detected in water source(s) consumed by 7% of cases and 3% of controls (cOR = 2.2; 95%CI 0.8-5.8).We used these findings to develop the first evidence-based guidelines for the prevention of melioidosis. These are suitable for people in melioidosis-endemic areas, travelers and military personnel. Public health campaigns based on our recommendations are under development in Thailand.